Analisis Framing Pemberitaan Pemberantasan Narkoba dan Rencana Strategi Humas Badan Narkotika Nasional - Raaf Ikhtsar Ismail; Iman Mukhroman; Ikhsan Ahmad (Jurnal Syntax Admiration, 2024)
This study discusses the role of public relations in planning communication strategies to handle news related to drug trafficking. Based on framing analysis from Antara and Detik.com media, it was found that these two media outlets highlighted drug trafficking as a serious threat, with news that focused on law enforcement actions and their social impact. Related to public relations strategy planning, the Ronald D. Smith model is used which includes four phases: formative research, strategy formulation, tactical implementation, and evaluation. The core of this study emphasizes the importance of structured and adaptive public relations strategic planning in dealing with drug trafficking issues, therefore it is necessary to increase cooperation with the media, adequate resource allocation, and the use of technology to reach a wider audience. Thus, it is hoped that drug eradication efforts can run more effectively and efficiently and get full support